The Role of Mobility and Sanitary Measures on the Delay of Community Transmission of COVID-19 in Costa Rica - Luis A. Barboza; Paola Vásquez; Gustavo Mery; Fabio Sanchez; Yury E. García; Juan G. Calvo; Tania Rivas; María Dolores Pérez; Daniel Salas (MDPI AG, 2021)
The aim of this paper is to infer the effects that change on human mobility had on the transmission dynamics during the first four months of the SARS-CoV-2 pandemic in Costa Rica, which could have played a role in delaying community transmission in the country. First, by using parametric and non-parametric change-point detection techniques, we were able to identify two different periods when the trend of daily new cases significantly changed. Second, we explored the association of these changes with data on population mobility. This also allowed us to estimate the lag between changes in human mobility and rates of daily new cases. The information was then used to establish an association between changes in population mobility and the sanitary measures adopted during the study period. Results showed that during the initial two months of the pandemic in Costa Rica, the implementation of sanitary measures and their impact on reducing human mobility translated to a mean reduction of 54% in the number of daily cases from the projected number, delaying community transmission.